2010
DOI: 10.1111/j.1095-8649.2010.02827.x
|View full text |Cite
|
Sign up to set email alerts
|

Has habitat heterogeneity promoted phenotypic and ecological sub‐structuring among a Coregonus lavaretus population in a large Scottish lake?

Abstract: Differences in stable-isotope values, morphology and ecology in whitefish Coregonus lavaretus were investigated between the three basins of Loch Lomond. The results are discussed with reference to a genetic investigation to elucidate any substructuring or spawning site fidelity. Foraging fidelity between basins of Loch Lomond was indicated by δ¹³C and δ¹⁵N values of C. lavaretus muscle tissue. There was, however, no evidence of the existence of sympatric morphs in the C. lavaretus population. A previous report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Some coregonid species have strong spawning site fidelity (Begout Anras, Cooley, Bodaly, Anras, & Fudge, ; Ebener, Brenden, Wright, Jones, & Faisal, ), which has implications especially in the conservation management of threatened populations (Hewitt & Winfield, ): individual spawning habitats demand preservation. However, Etheridge, Harrod, Bean, and Adams () did not observe spawning site fidelity in a whitefish ( Coregonus lavaretus : Salmonidae) population in Scotland. Conservation of particular habitats seems unnecessary for Finnish vendace populations where large potential spawning areas in lakes are available.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Some coregonid species have strong spawning site fidelity (Begout Anras, Cooley, Bodaly, Anras, & Fudge, ; Ebener, Brenden, Wright, Jones, & Faisal, ), which has implications especially in the conservation management of threatened populations (Hewitt & Winfield, ): individual spawning habitats demand preservation. However, Etheridge, Harrod, Bean, and Adams () did not observe spawning site fidelity in a whitefish ( Coregonus lavaretus : Salmonidae) population in Scotland. Conservation of particular habitats seems unnecessary for Finnish vendace populations where large potential spawning areas in lakes are available.…”
Section: Discussionmentioning
confidence: 96%
“…Integrated field sampling, 3‐D hydrodynamic modelling and spatial analysis gave unique knowledge about the small‐sized schooling coregonid species, which, as adults stay in the deep pelagic areas of the lake, highlights the unknowns in their reproductive strategy, spatial population structure and genetic diversity. Population sub‐structuring within a single species may have a number of important implications in fisheries management aiming to preserve the natural diversity of population (Etheridge et al., ). Furthermore, sympatric subpopulations may represent distinct evolutionary units and are important for the study of speciation (Etheridge et al., ; Helland, Harrod, Freyhof, & Mehner, ).…”
Section: Discussionmentioning
confidence: 99%
“…Etheridge et al . () showed structuring in foraging ecology in C. lavaretus across basins in Loch Lomond. Stable‐isotope ratios of C and N from muscle tissue of C. lavaretus in winter, indicative of the foraging pattern over the previous summer, differed between fish from the north, south and mid basins of Lomond.…”
Section: Discussionmentioning
confidence: 96%
“…As C. lavaretus appear to undergo a change in habit from pelagic to at least partly benthic foraging at c . 250 mm L F (Maitland, ; Etheridge et al ., 2010 a , b ), it seems likely that at this point C. lavaretus become vulnerable to L. fluviatilis . Coregonus lavaretus <250 mm are probably not exposed to foraging L. fluviatilis and so are rarely scarred.…”
Section: Frequency Of Historical (1951–1979) and Recent (2010) Lampetmentioning
confidence: 97%
“…Casual observation suggested that the number of C. lavaretus exhibiting evidence of L. fluviatilis feeding, collected from the lake during routine monitoring and other scientific studies in recent years, was remarkably low compared with past experience. Given the significant increase in scientific and conservation interest of both C. lavaretus (Etheridge et al ., 2010 a , b , 2011, 2012 a , b ) and L. fluviatilis populations of Loch Lomond (Adams et al ., ; Hume et al ., ) it was deemed an appropriate time to re‐examine the C. lavaretus population for L. fluviatilis ‐induced feeding scars (Maitland, ). Here evidence is presented that suggests a change in trophic interactions between L. fluviatilis and C. lavaretus that has occurred since the introduction of non‐native fish species to Loch Lomond, by comparing the proportion of C. lavaretus that were historically parasitized (pre‐1980) to the proportion parasitized in 2010.…”
Section: Frequency Of Historical (1951–1979) and Recent (2010) Lampetmentioning
confidence: 99%